2013
DOI: 10.5603/cj.a2017.0082
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging of intermediate lesions: Data from FFR, OCT, NIRS-IVUS

Abstract: The FFR-negative lesions pose traits of vulnerability as assessed simultaneously by IVUS, OCT and NIRS imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Thus it may affect final stent expansion and prone redistribution of LLB plaques to the edges of implanted stent edges to make space for the stent. Moreover, as it was shown a correlation between HLB lesions and thin fibrous cap atheroma (TFCA) [12,15], it is also possible that LLB lesions are less prone to embolization into the microcirculation from a thick cap. Indeed, OCT studies have shown that TFCA correlates with type IVa myocardial infarction after PCI [14], and OCT defined TFCA is a strong predictor of periprocedural infarction [10].…”
Section: Discussionmentioning
confidence: 99%
“…Thus it may affect final stent expansion and prone redistribution of LLB plaques to the edges of implanted stent edges to make space for the stent. Moreover, as it was shown a correlation between HLB lesions and thin fibrous cap atheroma (TFCA) [12,15], it is also possible that LLB lesions are less prone to embolization into the microcirculation from a thick cap. Indeed, OCT studies have shown that TFCA correlates with type IVa myocardial infarction after PCI [14], and OCT defined TFCA is a strong predictor of periprocedural infarction [10].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary angiography remains the gold standard for the diagnosis of CAD, however, its ability to differentiate ischemic from non-ischemic lesions is limited. In this respect, fractional flow reserve (FFR), which takes into consideration the functional severity of coronary stenosis, outperforms the traditional diagnostic approach, based solely on morphometric assessment [3,4]. Unfortunately, the adoption of FFR in everyday clinical practice is slow and is utilized in only a minority of centers [5,6].…”
Section: Introductionmentioning
confidence: 99%